2017
DOI: 10.1016/j.jcin.2016.12.015
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic Performance of Resting and Hyperemic Invasive Physiological Indices to Define Myocardial Ischemia

Abstract: The diagnostic performance of invasive physiological indices showed no differences in the prediction of myocardial ischemia defined by CFR. Using RFR as a reference, FFR showed a better discrimination and reclassification ability than resting indices.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
43
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 84 publications
(47 citation statements)
references
References 31 publications
2
43
0
1
Order By: Relevance
“…Although there has been only limited exploration of the relationships between the instantaneous wave-free ratio and MFR assessed by PET, 196 inconsistencies between the instantaneous wave-free ratio and FFR are common. [197][198][199] Nonetheless, two randomized trials have demonstrated that a strategy using an instantaneous wave-free ratio of more than 0.89 to defer revascularization yielded noninferior outcomes to a strategy using an FFR of more than 0.8.…”
Section: Ffrmentioning
confidence: 99%
“…Although there has been only limited exploration of the relationships between the instantaneous wave-free ratio and MFR assessed by PET, 196 inconsistencies between the instantaneous wave-free ratio and FFR are common. [197][198][199] Nonetheless, two randomized trials have demonstrated that a strategy using an instantaneous wave-free ratio of more than 0.89 to defer revascularization yielded noninferior outcomes to a strategy using an FFR of more than 0.8.…”
Section: Ffrmentioning
confidence: 99%
“…In this patient population, however, in which a low‐FFR value may have previously been rationalized away as an indirect sign of high flow and a healthy microcirculation, the (comparatively) unfavorable major adverse cardiac event (MACE) outcomes reported by Lee et al potentially imply an altogether different prognosis. The finding that, at 2‐year follow‐up, deferred angiographically insignificant stenosis with low FFR showed significantly higher event rates than those with high FFR (3.3% versus 1.2%; hazard ratio: 3.371; 95% confidence interval, 1.346–8.442; P =0.009) is very interesting, not least because it appears at odds with the oculostenotic reflex, the physiological mechanisms outlined above, and previous studies …”
Section: Vulnerable Plaque or Vulnerable End Point?mentioning
confidence: 54%
“…The problem for us as interventionalists is that we have become accustomed to thinking about ischemia in terms of hyperemic transstenotic pressure ratios; however, even quick revision of supply–demand mechanics reminds us that the ischemia results from a reduction in coronary flow, not simply a reduction in coronary pressure. This notion is supported by numerous studies in the literature that proved ischemia detection with FFR fallible to demonstrably high coronary flow situations …”
Section: Ffr: a Surrogate Measure Of Coronary Flowmentioning
confidence: 59%
“…However, this does not mean that each measurement cannot be similarly effective in guiding revascularization since their values are based on a physiologic response to a flow‐limiting stenosis. Pd/Pa and FFR have comparable diagnostic correlation when compared with PET‐derived coronary flow reserve which is regarded as the noninvasive gold‐standard to define myocardial ischemia . Overall, the clinical implication of the mismatch between Pd/Pa and FFR is unclear.…”
Section: Discussionmentioning
confidence: 99%
“…While the CV benefit of FFR is robust and iFR, the same cannot be said of Pd/Pa . However, Pd/Pa appears to have nearly identical reproducibility to iFR which does have randomized outcomes data in two large trials “iFR‐SWEDEHEART” and “DEFINE‐FLAIR” totaling 4529 patients . Investigation has suggested that the overall stenosis severity and association with major adverse cardiovascular events may be similar for Pd/Pa and iFR in some patient populations .…”
Section: Discussionmentioning
confidence: 99%